(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This study examines the structural-semantic classification of collocations as an important object of combinatorial linguistics. Collocations are viewed not as random word combinations, but as stable lexical units formed through grammatical patterns, semantic compatibility, and conventional language use. The aim of the research is to identify major structural models of collocations and analyze their semantic functions using examples from Uzbek, English, and Russian. The study applies descriptive, comparative, and structural methods. Particular attention is given to verb + noun, adjective + noun, noun + noun, and light verb constructions. The findings show that each model reflects specific semantic relations such as action, evaluation, nomination, and institutional meaning. Cross-linguistic comparison demonstrates that similar meanings may be expressed through different lexical patterns in different languages. It is concluded that the integration of structural and semantic approaches provides an effective basis for studying collocations in modern linguistics. The results may be useful for corpus studies, translation, lexicography, and language teaching.